2017
DOI: 10.1111/cas.13226
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine biomarkers to predict antitumor responses to nivolumab suggested in a phase 2 study for advanced melanoma

Abstract: Promising antitumor activities of nivolumab, a fully humanized IgG4 inhibitor antibody against the programmed death‐1 protein, were suggested in previous phase 1 studies. The present phase 2, single‐arm study (JAPIC‐CTI #111681) evaluated the antitumor activities of nivolumab and explored its predictive correlates in advanced melanoma patients at 11 sites in Japan. Intravenous nivolumab 2 mg/kg was given repeatedly at 3‐week intervals to 35 of 37 patients enrolled from December 2011 to May 2012 until they expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 24 publications
5
106
7
Order By: Relevance
“…There are active clinical trials for patients with solid tumors including HER2/neu-positive breast cancer using a bifunctional fusion protein (M7824) that combines the anti-PD-L1 antibody with the soluble extracellular domain of TGF-β receptor type II as a TGF-β-neutralizing "trap" (ClinicalTrials.gov identifiers NCT02517398, NCT02699515, and NCT03620201). 23 Although CXCL9 that was upregulated by PD-1/PD-L1 blockade was speculated to be driven by IFN-γ in melanoma, the results of the current study demonstrated no correlation between plasma CXCL9 and IFN-γ in patients with HCC as evidenced by no significant change in IFN-γ levels noted before and after treatment. 20 Murine colon carcinoma and breast cancer models further illustrated that M7824 attenuates tumor burden and enhances OS compared with TGF-β blockade alone, as evidenced by elevated CD8-positive T-cell and NK cell activation.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…There are active clinical trials for patients with solid tumors including HER2/neu-positive breast cancer using a bifunctional fusion protein (M7824) that combines the anti-PD-L1 antibody with the soluble extracellular domain of TGF-β receptor type II as a TGF-β-neutralizing "trap" (ClinicalTrials.gov identifiers NCT02517398, NCT02699515, and NCT03620201). 23 Although CXCL9 that was upregulated by PD-1/PD-L1 blockade was speculated to be driven by IFN-γ in melanoma, the results of the current study demonstrated no correlation between plasma CXCL9 and IFN-γ in patients with HCC as evidenced by no significant change in IFN-γ levels noted before and after treatment. 20 Murine colon carcinoma and breast cancer models further illustrated that M7824 attenuates tumor burden and enhances OS compared with TGF-β blockade alone, as evidenced by elevated CD8-positive T-cell and NK cell activation.…”
Section: Discussioncontrasting
confidence: 67%
“…6), which is consistent with the results of another study demonstrating increased serum CXCL9 levels in patients with advanced melanoma after treatment with nivolumab. 23 Although CXCL9 that was upregulated by PD-1/PD-L1 blockade was speculated to be driven by IFN-γ in melanoma, the results of the current study demonstrated no correlation between plasma CXCL9 and IFN-γ in patients with HCC as evidenced by no significant change in IFN-γ levels noted before and after treatment. Therefore, the plasma CXCL9 concentration may be altered by other cytokines, including IL-27, which has been reported to regulate CXCL9 expression in patients with hepatitis.…”
Section: Discussioncontrasting
confidence: 67%
“…Furthermore, the expression of these cytokines, together with IFNγ and granzymes, is strongly correlated with the expression of PD-L1 tumors, suggesting the potential benefit of checkpoint blockade (68). Successful melanoma and renal cell carcinoma clinical trials reported the association of intratumoral CXCL9 and CXCL10 in TILs with clinical benefit from adoptive T cell therapy (69), ipilimumab (70,71) and pembrolizumab (72), as well as the increase of circulating CXCL9 and CXCL10 during treatment with nivolumab (73,74). The early phase checkpoint inhibitor trials in OC demonstrated a durable antitumor response in some patients [reviewed in (75)].…”
Section: Discussionmentioning
confidence: 99%
“…It can therefore be assumed that there are patient groups who are unlikely to respond to anti‐PD‐1 antibody monotherapy or nivolumab plus ipilimumab. In Japanese phase II clinical trials, ORRs to Nivolumab were 28.6% in previously treated advance melanoma and 34.8% in treatment‐naïve advanced melanoma, and ORR of 10.0% and BOR of 20.0% to ipilimumab were reported …”
Section: Discussionmentioning
confidence: 99%